Kebiasaan Membaca Label Informasi Gizi dan Pengaruhnya terhadap Obesitas : Sebuah Literature Review - Salwa Alina Faza; Dian Isti Angraini; Sofyan Musyabiq Wijaya; Bayu Anggileo Pramesona (CV. Jasa Sukses Abadi, 2026)
Obesity is a growing global health problem, including in Indonesia. One preventative strategy is through the habit of reading nutritional information labels on packaged food products, which provide information on energy, fat, sugar, and sodium content. However, this habit remains low and has not been directly studied in relation to obesity incidence. This study is a literature review of articles from the Google Scholar, PubMed, ScienceDirect, and GARUDA databases from 2015–2025. Keywords used include